PENANGANAN TERSANGKA KELOMPOK SEPARATIS DALAM MEWUJUDKAN PERLINDUNGAN HAK ASASI MANUSIA BERDASARKAN PRINSIP KEADILAN (STUDI KASUS PENUGASAN DAERAH PAPUA) - Zulfikar; Muhamad Aminulloh; mulyadi (JURNAL ILMIAH LIVING LAW, 2023)
: This article presents crimes committed by separatist groups which often result in human rights violations in the Papua region. This study illustrates how the case ultimately brought legal consequences for the separatist group. This resulted in the creation of the desires of the separatist groups, namely their own desire to disturb security, the desire to be independent apart from the unitary state of the Republic of Indonesia. The author realizes that the analysis of the data obtained is practice-oriented which allows understanding of how some of the group's criminalized acts were transformed into 'hate crimes'. In addition, several cases were conducted in court. The results of the study show that the handling of suspected separatist groups to implement human rights protection in accordance with the principles of justice in the mission of the Papua region through various government conflict resolution approaches has been widely applied in Papua.